Identification of the strain-specifically truncated nonstructural protein 10 of porcine reproductive and respiratory syndrome virus in infected cells - ZHANG, Zhi-bang; XU, Lei; WEN, Xue-xia; DONG, Jian-guo; ZHOU, Lei; GE, Xin-na; YANG, Han-chun; GUO, Xin (Journal of Integrative Agriculture, 2018)
The nonstructural protein 10 (nsp10) of porcine reproductive and respiratory syndrome virus (PRRSV) encodes for helicase which plays a vital role in viral replication. In the present study, a truncated form of nsp10, termed nsp10a, was found in PRRSV-infected cells and the production of nsp10a was strain-specific. Mass spectrometric analysis and deletion mutagenesis indicated that nsp10a may be short of about 70 amino acids in the N terminus of nsp10. Further studies by rescuing recombinant viruses showed that the Glu-69 in nsp10 was the key amino acid for nsp10a production. Finally, we demonstrated that nsp10a exerted little influence on the growth kinetics of PRRSV